2022
DOI: 10.1101/2022.05.30.22275704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipidome- and genome-wide study to understand sex differences in circulatory lipids

Abstract: Despite well-recognized difference in the atherosclerotic cardiovascular disease (ASCVD) risk between men and women, sex differences in risk factors and sex specific mechanisms in the pathophysiology of ASCVD remain poorly understood. Lipid metabolism plays a central role in the development of ASCVD. Understanding sex differences in lipids and their genetic determinants could provide mechanistic insights into sex differences in ASCVD and aid in precise risk assessment. Thus, we examined sex differences in plas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
1
0
0
Order By: Relevance
“…We found that lipid species, which were differently associated with AgeAccelPheno and AgeAccelGrim in men and women, predominately belonged to TAG and some phospholipid species (Figure S4), which is in line with reports from previous studies (Gonzalez-Covarrubias et al, 2013;Hoene et al, 2014;Tabassum et al, 2022).…”
Section: Sex Interaction and Sex-stratified Analysessupporting
confidence: 91%
“…We found that lipid species, which were differently associated with AgeAccelPheno and AgeAccelGrim in men and women, predominately belonged to TAG and some phospholipid species (Figure S4), which is in line with reports from previous studies (Gonzalez-Covarrubias et al, 2013;Hoene et al, 2014;Tabassum et al, 2022).…”
Section: Sex Interaction and Sex-stratified Analysessupporting
confidence: 91%
“…The study protocols were approved by The Hospital District of Helsinki and Uusimaa Coordinating Ethics committees (approval No.∼281/13/03/00/14 (GeneRISK)). Mass spectrometry-based lipid analysis was performed for 7302 individuals from the GeneRISK cohort by shotgun lipidomic analysis at Lipotype GmbH (Dresden, Germany) [6,7].…”
Section: Datasetsmentioning
confidence: 99%